2021
DOI: 10.3390/ma14112902
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Improvement of Eutectic Al + Mg2Si Phases on Al–Zn–Si–Mg Cast Alloy with TiB2 Particles Additions

Abstract: In this study, the effects of adding TiB2 particles to eutectic Al + Mg2Si phases in aluminum alloys were analyzed. The eutectic Al + Mg2Si phases were modified effectively when a large amount of TiB2 was added, and changes in the shape, size, and distribution of the eutectic Al + Mg2Si phases were confirmed using a polarizing microscope and FE-SEM. The crystal structure of the TiB2 particles and Mg2Si phases were analyzed using HR-TEM, and the analysis confirmed that the TiB2 particles can act as heterogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In addition, the Mg and Si atoms in this alloy crystallized according to the composition ratio and Mg 2 Si phase led to precipitation strengthening [ 29 ]. Factors contributing to the alloy strength of the Al chips produced by the SS process include matrix spheroidization and precipitated Mg 2 Si phase formation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the Mg and Si atoms in this alloy crystallized according to the composition ratio and Mg 2 Si phase led to precipitation strengthening [ 29 ]. Factors contributing to the alloy strength of the Al chips produced by the SS process include matrix spheroidization and precipitated Mg 2 Si phase formation.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the Al 10 Mn 3 particle is a better nucleating site for α-Mg grains than the Al 8 Mn 5 particle, and α-Mg can nucleate on the Al 10 Mn 3 nucleation substrates. Previous research has shown that a substrate can effectively act as a nucleant for a solid if the disregistry between the two is less than 5% [ 36 ]. However, this is not always the case.…”
Section: Discussionmentioning
confidence: 99%
“…The present study aims to manufacture a high-strength aluminum alloy with improved mechanical properties through the SSP. The Al chips used in this study are made from the Al alloy developed by Kim et al [19,20]. The alloy contains eutectic Mg 2 Si particles, which are considered to be the main reinforcement phase to increase mechanical properties.…”
Section: Introductionmentioning
confidence: 99%